A Study on Improving Metamemory through Cognitive Language Activities Worksheets among Individuals with psychosomatic symptoms - Monika, Monika; Suganthan, C. (Utan Kayu Publishing, 2024)
Psychosomatic condition refers to mental and physical dysfunction arising from physical and psychological symptoms. This research aims to employ cognitive language activities to increase and improve the participants' metamemory who have a psychosomatic illness. Engineering students from the Vellore region studying at the tertiary level were selected as the study participants. Participants in late adolescence were chosen for the study because they displayed a high level of psychosomatic condition. The study employs a non-equivalent control group Design (NEGD), which incorporates both qualitative and quantitative analysis, as the study involves non-randomization,and contest the variables. The sampling method employed in the study is purposive sampling hence, non-parametric test was performed in SPSS. Unstructured interview was also employed after each session and their symptoms were inquired and marked in PSQ. Participants were given and instructed to employ coping startegies and memory strategies to reduce the impact of memory decline, psychosomatic symptoms, stress and anxiety. The intervention took place over eight weeks, and participants were given four sets of worksheets like chunking and embroidery. To assess the participants' progress, eight successive tests were administered. Ninety-three people were chosen to participate in the current study. The pre-test and post-test scores' significant value was 0.000. The results indicate a substantial difference between the metamemory pre-test and post-test scores. Cognitive activities have significantly triggered the pre-frontal cortex region of the brain (responsible for memory and have negative effect due to psychosomatic condition) and improved the metamemory and memory strategies.